Elizabeth I, red rose of the House of Tudor - Lasky, Kathryn (New York : Scholastic, 1999)
In a series of diary entries, Princess Elizabeth, the eleven-year-old daughter of King Henry VIII, celebrates holidays and birthdays, relives her mother's execution, revels in her studies, and agonizes over her father's health.
"England, 1544"--Cover.
820
Accelerated Reader AR
Keywords: Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Childhood and youth -- Juvenile fiction; Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Childhood and youth -- Fiction; Princesses -- Fiction; Diaries -- Fiction; Great Britain -- History -- Henry VIII, 1509-1547 -- Juvenile fiction; Great Britain -- History -- Henry VIII, 1509-1547 -- Fiction; Kings, queens, rulers, etc. -- Fiction